Cerium-containing α-calcium sulfate hemihydrate bone substitute promotes osteogenesis. (August 2019) - Xiang, Haibo; Wang, Yu; Chang, Hong; Yang, Shenyu; Tu, Mei; Zhang, Xianrong; Yu, Bin
Bone substitute offers a promising strategy for the reconstruction of large bone defects. It may be feasible to develop a better substitute material by enhancing the osteoinductivity and delaying the degradation of α-calcium sulfate hemihydrate. In this study, nano cerium oxide was incorporated with α-calcium sulfate hemihydrate at weight ratios of 5 and 10% to form nano cerium oxide-containing α-calcium sulfate hemihydrate. Extracts from α-calcium sulfate hemihydrate, 5 and 10% nano cerium oxide-containing α-calcium sulfate hemihydrate were prepared for in vitro treatment of cells. After critical bone defects were made on the left tibia of male Sprague–Dawley rats, the animals were randomly divided into four groups subjected to the filling with nothing (blank), α-calcium sulfate hemihydrate (control), 5 and 10% nano cerium oxide-containing α-calcium sulfate hemihydrate. Extraction from 5% nano cerium oxide-containing α-calcium sulfate hemihydrate composite stimulated cells proliferation and increased cell migration and mRNA expression of osteoblastic marker genes in primary bone marrow stromal cells. X-ray and micro-computed tomography analyses showed increased bone formation and reduced degradation, and histological analysis showed mineralized staining on the boundary area between composites and bone marrow in the nano cerium oxide-containing α-calcium sulfate hemihydrate group. Immunostaining of osteocalcin confirmed the increased bone formation in the nano cerium oxide-containing α-calcium sulfate hemihydrate group. Nano cerium oxide-containing α-calcium sulfate hemihydrate composite with 5% w/w nano cerium oxide showed a better capacity of enhancing osteogenesis and bone regeneration model than 10% cerium oxide-containing α-calcium sulfate hemihydrate composite. The findings suggested that the nano cerium oxide-containing α-calcium sulfate hemihydrate might be a potential material for bone substitutes since it may promote local bone regeneration.